Battery, battery pack and electric device

By adjusting the viscosity and injection coefficient of the electrolyte, as well as the compaction density of the positive electrode sheet, it meets the specific formula relationship, the problem of degradation of the electrolyte's wettability is solved, and high energy density and optimized cycling performance are achieved.

CN119627181APending Publication Date: 2025-03-14EVE POWER CO LTD

Patent Information

Application Number
CN202411748649.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

While improving the electrode sheet density and compaction density in lithium batteries, it is difficult to maintain good wetting properties of the electrolyte on the electrode sheet, affecting the kinetic performance and cycle life.

Method used

By adjusting the viscosity of the electrolyte, the injection coefficient and the compaction density of the positive electrode sheet, it satisfies the specific formula relationship to ensure sufficient wetting of the electrolyte on the electrode sheet.

Benefits of technology

While increasing the energy density, the negative impact caused by the increase in compaction density and surface density is reduced, the charge transfer efficiency and cycling performance are improved, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627181A_ABST
    Figure CN119627181A_ABST
Patent Text Reader

Abstract

The invention provides a battery, a battery pack and a power utilization device, and belongs to the technical field of batteries, the battery comprises a positive plate, a negative plate and an electrolyte; the battery meets the following conditions: # imgabs0 #, V represents the viscosity of the electrolyte, and the unit is mPa.s; pD represents the compaction density of the positive plate, and the unit is g / cm < 3 >; c represents the liquid injection coefficient of the electrolyte, and the unit is g / Ah. According to the battery provided by the embodiment of the invention, by meeting the formula, the good wettability of the electrolyte on the positive plate can be ensured under the condition that the compaction density and the surface density of the positive plate in the battery are relatively high, so that the negative influence caused by the improvement of the compaction density and the surface density is reduced while the battery has high energy density, and the service life of the battery is prolonged. The charge transfer efficiency is improved, the battery cycle performance is optimized, the battery power density is improved, and the comprehensive performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a battery, a battery pack and an electrical device. Background Art

[0002] With the rapid development of new energy vehicles, how to improve the range of new energy vehicles and reduce the charging time of new energy vehicles has become the main problem that needs to be solved in the current development process of new energy vehicles.

[0003] In order to improve the range of new energy vehicles, it is necessary to improve the energy density of power batteries. In the relevant technology, increasing the surface density and compaction density of the battery pole piece is an important means to improve the energy density of lithium batteries. However, with the increase of the surface density and compaction density of the battery pole piece, it is easy to cause the wettability of the electrolyte to the pole piece to decrease, thereby affecting the dynamic performance of the battery, and also having an adverse effect on the battery fast charging performance and cycle life. Summary of the invention

[0004] The embodiments of the present application provide a battery, a battery pack and an electrical device, which can improve the surface density and compaction density of the battery electrode while ensuring sufficient infiltration of the electrode by the electrolyte.

[0005] In a first aspect, an embodiment of the present application provides a battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0006] The battery satisfies the following formula:

[0007]

[0008] Where V represents the viscosity of the electrolyte, in mPa·s; PD represents the compaction density of the positive electrode, in g / cm 3 ; C represents the electrolyte filling coefficient, the unit is g / Ah.

[0009] In some embodiments, the battery satisfies the following formula:

[0010]

[0011] In some embodiments, the viscosity V of the electrolyte and the compaction density PD of the positive electrode sheet satisfy the following formula:

[0012] V = aPD + b;

[0013] Among them, -5.0≤a≤-4.0, 10≤b≤20.

[0014] In some embodiments, -4.7≤a≤-4.3, 13≤b≤16.

[0015] In some embodiments, the viscosity V of the electrolyte satisfies: 2.5 mPa·s≤V≤4.0 mPa·s;

[0016] And / or, the electrolyte injection coefficient C satisfies: 2.5g / Ah≤C≤4.5g / Ah;

[0017] And / or, the compaction density PD of the positive electrode sheet meets: 2.2g / cm 3 ≤PD≤2.8g / cm 3 .

[0018] In some embodiments, the viscosity V of the electrolyte satisfies: 3.2 mPa·s≤V≤3.6 mPa·s;

[0019] And / or, the electrolyte injection coefficient C satisfies: 2.8g / Ah≤C≤3.5g / Ah;

[0020] And / or, the compaction density PD of the positive electrode sheet meets: 2.3g / cm 3 ≤PD≤2.6g / cm 3 .

[0021] In some embodiments, the viscosity of the electrolyte is the viscosity of the electrolyte at 25°C;

[0022] The compaction density of the positive electrode sheet is the compaction density of the positive electrode sheet in an empty and charged state.

[0023] In some embodiments, the electrolyte includes a lithium salt and a solvent;

[0024] The solvent includes at least one of dimethyl carbonate, ethylene carbonate, propylene carbonate, ethyl methyl carbonate, ethyl acetate and fluoroethylene carbonate.

[0025] In some embodiments, the solvent includes dimethyl carbonate, and the mass proportion of dimethyl carbonate in the solvent is ≤50%.

[0026] In some embodiments, the single-sided surface density of the positive electrode sheet is 150 g / m 2 -300 g / m 2 .

[0027] In some embodiments, the positive electrode active material in the positive electrode sheet includes one of lithium iron phosphate and lithium manganese iron phosphate.

[0028] In some embodiments, the negative electrode active material in the negative electrode sheet includes graphite;

[0029] And / or, the single surface density of the negative electrode sheet is 80g / m 2 -120 g / m 2 ;

[0030] And / or, the compaction density of the negative electrode sheet is 1.45 g / cm 3 -1.70g / cm 3 .

[0031] In some embodiments, the ratio of the negative electrode capacity to the positive electrode capacity of the battery is 1.05-1.25.

[0032] In some embodiments, the ratio of the negative electrode capacity to the positive electrode capacity of the battery is 1.10-1.15.

[0033] In some embodiments, the energy density of the battery is 150Wh / kg-250Wh / kg.

[0034] In a second aspect, an embodiment of the present application provides a battery pack, comprising a battery as described above.

[0035] In a third aspect, an embodiment of the present application provides an electrical device, comprising a battery as described above, and / or a battery pack as described above.

[0036] Beneficial effects of the embodiments of the present application:

[0037] In the battery provided in the embodiment of the present application, the viscosity of the electrolyte in the battery, the injection coefficient of the electrolyte and the compaction density of the positive electrode sheet satisfy the formula It can ensure that the electrolyte has good wettability to the positive electrode sheet while the compaction density and surface density of the positive electrode sheet in the battery are high, so that the battery has a high energy density while reducing the negative impact caused by the increase in compaction density and surface density, increasing the charge transfer efficiency, optimizing the battery cycle performance, improving the battery power density, and improving the overall performance of the battery. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0039] In a first aspect, an embodiment of the present application provides a battery, including a positive electrode sheet, a negative electrode sheet and an electrolyte. The battery satisfies Formula 1:

[0040]

[0041] Where V represents the viscosity of the electrolyte, in mPa·s; PD represents the compaction density of the positive electrode, in g / cm 3; C represents the electrolyte filling coefficient, the unit is g / Ah.

[0042] It should be noted that the viscosity of the electrolyte refers to the physical quantity of the internal friction resistance or the degree of flow difficulty exhibited by the electrolyte when it flows, which is one of the important indicators for measuring the flow performance of the electrolyte. The viscosity of the electrolyte is affected by many factors such as the type and concentration of ions in the electrolyte, the properties of the solvent, and the temperature. The higher the viscosity of the electrolyte, the slower the wetting speed of the electrode and the more difficult it is to diffuse. The lower the viscosity of the electrolyte, the faster the wetting speed of the electrode and the easier it is to diffuse. The viscosity of the electrolyte in the embodiment of the present application refers to the viscosity of the electrolyte at room temperature (ie, 25°C).

[0043] The electrolyte injection coefficient refers to the amount of electrolyte injection determined according to the cell capacity during the battery manufacturing process. For example, if the cell capacity is 100Ah and the injection coefficient is 3.0, 300g of electrolyte should be injected. The unit of the injection coefficient is g / Ah. Too high or too low an injection coefficient is not conducive to the battery's cycle performance.

[0044] The compaction density of the positive electrode sheet refers to the degree to which it is tightly compacted during the production process of the positive electrode sheet. Generally, an increase in the compaction density will increase the capacity and energy density of the battery. The compaction density of the positive electrode sheet in the embodiment of the present application refers to the compaction density of the battery in an empty state. Among them, the empty state refers to the state when the battery is discharged to the cut-off voltage. The cut-off voltage is related to the selection of the positive electrode active material in the positive electrode sheet and the ambient temperature. For example, for batteries whose positive electrode active materials are lithium iron phosphate and lithium iron manganese phosphate, at room temperature (ie 25°C), the empty state refers to the state when the battery is discharged to 2.5V, and at 0°C, the empty state refers to the state when the battery is discharged to 2.0V. The compaction density of the positive electrode sheet can be obtained by measuring the surface density and thickness of the electrode sheet and calculating it.

[0045] In the related art, in order to improve the energy density of the battery, the compaction density of the positive electrode sheet is usually increased. After the compaction density of the positive electrode sheet is increased, on the one hand, the porosity of the positive electrode sheet will be reduced, making it difficult for the electrolyte to penetrate into the interior of the positive electrode sheet, resulting in a poor infiltration effect. On the other hand, in the process of increasing the compaction density, the pores between the particles in the positive electrode sheet will also be deformed due to extrusion, resulting in an increase in the tortuosity of the pores, which in turn increases the difficulty of the electrolyte diffusing in the positive electrode sheet. Therefore, the increase in the compaction density of the positive electrode sheet is likely to lead to a poor infiltration performance of the electrolyte on the positive electrode sheet.

[0046] After in-depth research, the inventors found that by properly controlling the viscosity V and injection coefficient C of the electrolyte and the compaction density PD to satisfy the above formula 1, it is possible to ensure that the wetting performance of the electrolyte on the positive electrode sheet is maintained within a reasonable range and reduce the negative impact of increased compaction density on the battery's new energy.

[0047] In some embodiments, the battery satisfies the following formula 2:

[0048]

[0049] By making the viscosity V of the electrolyte, the compaction density PD of the positive electrode sheet and the injection coefficient C of the electrolyte satisfy Formula 2, the wetting performance of the electrolyte on the positive electrode sheet can be further guaranteed, so that the battery can improve the energy density by increasing the compaction density while ensuring the charge transfer efficiency in the battery, and the cycle performance, that is, the power density.

[0050] In some embodiments, the viscosity V of the electrolyte and the compaction density PD of the positive electrode sheet satisfy the following formula 3:

[0051] V=aPD+bFormula 3;

[0052] Among them, -5.0≤a≤-4.0, 10≤b≤20.

[0053] That is to say, the viscosity V of the electrolyte and the compaction density PD of the positive electrode sheet show a negative correlation trend. As mentioned above, when the compaction density of the positive electrode sheet increases, it is easy to cause the porosity of the positive electrode sheet to decrease, that is, the pores are deformed. By reducing the viscosity of the electrolyte, the viscosity of the electrolyte can be improved, and it is easier to penetrate into the pores of the positive electrode sheet, so that the active materials in the positive electrode sheet can participate in the electrochemical reaction more fully.

[0054] The embodiment of the present application ensures that the viscosity V of the electrolyte and the compaction density PD of the positive electrode sheet satisfy the above formula three, which can not only ensure the wetting performance of the electrolyte on the positive electrode sheet, but also make the ion distribution in the electrolyte more uniform, thereby ensuring the ion conduction efficiency, and maintaining good stability of the electrolyte, thereby improving the cycle performance of the battery.

[0055] In some embodiments, -4.7≤a≤-4.3, 13≤b≤16.

[0056] After in-depth research, the inventors found that when the three parameters a and b of the formula are controlled within this range, the wetting performance of the electrolyte on the positive electrode sheet can be guaranteed, and the negative impact caused by the low viscosity of the electrolyte can be reduced.

[0057] Furthermore, the viscosity V of the electrolyte and the compaction density PD of the positive electrode sheet satisfy the following formula 4:

[0058] V=-4.6PD+14.903Formula 4;

[0059] Among them, the correlation coefficient R of this equation 2 =0.985.

[0060] For example, when the compaction density PD of the positive electrode sheet is 2.55 g / cm3 When the electrolyte viscosity is 3.19 mPa·s, the compaction density PD of the positive electrode is 2.50 g / cm 3 When the electrolyte viscosity is 3.37 mPa·s, the compaction density PD of the positive electrode is 2.45 g / cm 3 When , the viscosity of the electrolyte can be 3.65 mPa·s.

[0061] In some embodiments, the viscosity V of the electrolyte satisfies: 2.5 mPa·s≤V≤4.0 mPa·s.

[0062] By controlling the viscosity of the electrolyte within the above range, the electrolyte has a moderate barrier effect on ions, so that the charge transfer speed in the electrolyte is relatively fast, which helps to improve the charge and discharge efficiency of the battery and enables the battery to respond to load changes more quickly. The friction resistance inside the electrolyte is also small, which can reduce the internal resistance of the battery. The above viscosity range also helps to maintain the stability of the electrolyte during the battery cycle and reduce the decomposition and side reactions of the electrolyte. In addition, the viscosity of the electrolyte is within the above range, which can ensure that the electrolyte has good thermal stability, help reduce the safety risks of the battery at high temperatures, and improve the safety performance of the battery.

[0063] In some embodiments, the electrolyte injection coefficient C satisfies: 2.5 g / Ah≤C≤4.5 g / Ah.

[0064] When the electrolyte injection coefficient is within the above range, the electrolyte wetting performance can be guaranteed, the electrochemical reaction inside the battery can be promoted, the battery charging and discharging efficiency and energy density can be improved, the battery stability during the cycle can be maintained, and the decomposition of the electrolyte and the occurrence of side reactions can be reduced. In addition, controlling the electrolyte injection coefficient within the above range can also ensure the battery cycle performance.

[0065] In some embodiments, the compaction density PD of the positive electrode sheet satisfies: 2.2 g / cm 3 ≤PD≤2.8g / cm 3 .

[0066] By controlling the compaction density of the positive electrode sheet within the above range, the active materials in the positive electrode sheet can be fully utilized, thereby improving the energy density and capacity of the battery. A higher compaction density makes the contact between the active materials closer, which is conducive to the insertion and extraction of lithium ions, thereby improving the specific capacity of the battery.

[0067] In some embodiments, the viscosity V of the electrolyte satisfies: 3.2 mPa·s≤V≤3.6 mPa·s.

[0068] By controlling the viscosity of the electrolyte within this range, the performance of the battery can be further improved, which will not be elaborated here.

[0069] In some embodiments, the electrolyte injection coefficient C satisfies: 2.8g / Ah≤C≤3.5g / Ah.

[0070] By controlling the electrolyte injection coefficient within this range, the battery performance can be further improved and the battery cycle performance can be guaranteed, which will not be elaborated here.

[0071] In some embodiments, the compaction density PD of the positive electrode sheet satisfies: 2.3 g / cm 3 ≤PD≤2.6g / cm 3 .

[0072] By controlling the compaction density of the positive electrode sheet within this range, the performance of the battery can be further improved, which will not be elaborated here.

[0073] In some embodiments, the electrolyte includes a lithium salt and a solvent, wherein the solvent includes at least one of dimethyl carbonate (DMC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), ethyl acetate (EA) and fluoroethylene carbonate (FB).

[0074] The lithium salt in the electrolyte can provide lithium ions to ensure the charge conduction efficiency of the electrolyte, while the solvent can dissolve the lithium salt to ensure that the electrolyte has appropriate viscosity, stability and other properties.

[0075] In the embodiment of the present application, the solvent in the electrolyte includes at least one of dimethyl carbonate, ethylene carbonate, propylene carbonate, ethyl methyl carbonate, ethyl acetate and fluoroethylene carbonate. These solvents all have high ionic conductivity, contribute to the dissolution of lithium salts and the conduction of ions, and have good electrochemical stability, are not prone to decomposition or side reactions, and have good compatibility with electrode materials, and contribute to the formation of a stable solid electrolyte interface (SEI) film on the electrode surface. By adjusting the composition and proportion of the solvent, the electrolyte can have a suitable viscosity.

[0076] In some embodiments, the solvent includes dimethyl carbonate (DMC), and the mass proportion of dimethyl carbonate in the solvent is ≤50%.

[0077] The viscosity of dimethyl carbonate is relatively small. By including dimethyl carbonate in the solvent, the viscosity of the solvent can be adjusted to meet the viscosity range required by the embodiment of the present application. It is understandable that the higher the addition ratio of dimethyl carbonate, the lower the viscosity of the electrolyte, the better the wetting effect on the positive and negative plates in the battery, and the more suitable it is for a battery system with a high compaction density.

[0078] In addition, although dimethyl carbonate can reduce the viscosity of the electrolyte, in order to ensure that the electrolyte has better electrochemical stability and better conductivity efficiency, the mass ratio of dimethyl carbonate in the solvent is controlled below 50%.

[0079] In some embodiments, the mass proportion of dimethyl carbonate in the solvent is ≤30%.

[0080] In some embodiments, the single-sided surface density of the positive electrode sheet is 150 g / m 2 -300 g / m 2 .

[0081] Controlling the single-sided surface density of the positive electrode sheet within the above range can improve the quality of the active material in the positive electrode sheet, which in turn helps to improve the energy density of the battery, allowing the battery to store more energy at the same volume or weight. In addition, the single-sided surface density of the positive electrode sheet is also related to the power density of the battery. Within the above range, it can shorten the migration path of lithium ions, reduce the internal resistance of the battery, and thus improve the power transmission capacity of the battery. A relatively high single-sided surface density can also make the structure of the positive electrode sheet more compact and reduce the structural damage caused by volume changes during battery charging and discharging.

[0082] In some embodiments, the positive electrode active material in the positive electrode sheet includes one of lithium iron phosphate and lithium manganese iron phosphate.

[0083] Lithium iron phosphate (LFP) and lithium manganese iron phosphate (LMFP) are both olivine-type positive electrode active materials with stable crystal structures, which help maintain the integrity of the materials during the charge and discharge process and improve the cycle stability and service life of the battery. In addition, both lithium iron phosphate and lithium manganese iron phosphate have good high-temperature stability and are not prone to thermal runaway or fire.

[0084] In addition, there are certain differences in the performance of lithium iron phosphate and lithium iron manganese phosphate. For example, lithium iron manganese phosphate has a higher voltage platform and higher theoretical energy density than lithium iron phosphate. In order to further improve the energy density of the battery and ensure the wetting performance of the electrolyte, different positive electrode sheet compaction densities can be set according to the selection of positive electrode active materials. For example, when the positive electrode active material is lithium iron phosphate, the compaction density of the positive electrode sheet can be set to 2.3g / cm 3 -2.4g / cm 3 When the positive electrode active material is lithium manganese iron phosphate, the compaction density of the positive electrode sheet can be set to 2.4g / cm 3 -2.55g / cm 3 .

[0085] In some embodiments, the negative electrode active material in the negative electrode sheet includes graphite. Graphite has a high theoretical lithium insertion capacity, which helps to improve the energy density of the battery. In addition, the lithium insertion potential of graphite is low, which helps to reduce the polarization phenomenon of the battery during the charging and discharging process and improve the working efficiency of the battery. Graphite also has good cycle stability, stable structure, and high thermal stability.

[0086] In some embodiments, the single-sided surface density of the negative electrode sheet is 80 g / m 2 -120 g / m 2 .

[0087] When the single-sided surface density of the negative electrode sheet is within the above range, it helps to ensure the balance between the battery energy density and power density, and makes the structure of the negative electrode sheet more compact, the distribution of active materials more uniform, and helps to reduce the structural damage caused by volume changes during the charging and discharging process, thereby improving the cycle stability of the battery. In addition, within the above range, it is also possible to balance the energy density and safety of the battery, reduce the internal resistance and heat generation of the battery, and ensure the safety of the battery.

[0088] In some embodiments, the compaction density of the negative electrode sheet is 1.45 g / cm 3 -1.70g / cm 3 .

[0089] Compaction density is one of the important factors affecting battery energy density. When the compaction density of the negative electrode sheet is within the above range, it can improve the energy density of the battery, and also help maintain the stability and integrity of the negative electrode sheet structure, facilitate the rapid embedding and extraction of lithium ions, reduce the internal resistance of the battery, and improve the power output capacity and response speed of the battery.

[0090] In some embodiments, the ratio of the negative electrode capacity to the positive electrode capacity (NP ratio) of the battery is 1.05-1.25.

[0091] The increase in negative electrode capacity relative to positive electrode capacity enables the battery to more effectively utilize active materials during the charge and discharge process, thereby increasing the battery's energy density. A higher NP ratio helps reduce the battery's internal resistance, improves the battery's output capacity and response speed, and enables the battery to perform better in application scenarios that require high power output.

[0092] In some embodiments, the ratio of the negative electrode capacity to the positive electrode capacity of the battery is 1.10-1.15. That is, the NP ratio is preferably set within this range to further improve the energy density, output capacity and response speed of the battery.

[0093] In some embodiments, the energy density of the battery is 150Wh / kg-250Wh / kg.

[0094] Batteries with high energy density can store more energy at the same weight, thereby extending the range and time of new energy vehicles and other equipment. In addition, batteries with high energy density can support higher power output, allowing the equipment to perform better in application scenarios that require high power output. At the same time, batteries with high energy density usually have faster charging speeds, which helps shorten the charging time of the device.

[0095] The embodiment of the present application makes the viscosity V of the electrolyte, the compaction density PD of the positive electrode sheet and the injection coefficient C of the electrolyte satisfy Formula 1, so that the battery can maintain the wettability of the electrolyte while having a high energy density, thereby improving the overall performance of the battery.

[0096] In a second aspect, an embodiment of the present application provides a battery pack, comprising the above-mentioned battery. The battery pack provided by the embodiment of the present application has all the beneficial effects of the above-mentioned battery, which will not be described in detail here.

[0097] In a third aspect, an embodiment of the present application provides an electric device, including the above-mentioned battery and / or the above-mentioned battery pack. The electric device provided by the embodiment of the present application has all the beneficial effects of the above-mentioned battery, which will not be described in detail here.

[0098] The following examples are further described in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on the conditions recommended by the manufacturer.

[0099] Example 1

[0100] Lithium iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0101] Graphite is used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry is coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet is 99 g / m 2 , compacted density is 1.65g / cm 3 ;

[0102] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0103] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0104] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0105] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate, 35 parts of ethyl methyl carbonate and 30 parts of dimethyl carbonate, and the viscosity of the electrolyte is 3.24;

[0106] The electrolyte was injected into the vacuum-baked battery and allowed to stand for 10 hours to allow the electrolyte to fully infiltrate the positive electrode sheet, the negative electrode sheet and the separator; wherein the electrolyte injection coefficient was 3.10 mPa·s;

[0107] The battery after the electrolyte is injected is charged for the first time and formed;

[0108] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0109] Example 2

[0110] Lithium manganese iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.32g / cm 3 ;

[0111] Graphite was used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry was coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet was 93 g / m 2 , compacted density is 1.65g / cm 3 ;

[0112] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0113] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0114] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0115] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate, 25 parts of ethyl methyl carbonate and 40 parts of dimethyl carbonate, and the viscosity of the electrolyte is 3.19 mPa·s;

[0116] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully soak the positive electrode sheet, negative electrode sheet and separator; wherein the electrolyte injection coefficient is 3.25;

[0117] The battery after the electrolyte is injected is charged for the first time and formed;

[0118] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0119] Example 3

[0120] Lithium iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0121] Graphite is used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry is coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet is 99 g / m 2 , compacted density is 1.65g / cm 3 ;

[0122] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0123] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0124] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0125] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate, 25 parts of ethyl methyl carbonate and 40 parts of dimethyl carbonate, and the viscosity of the electrolyte is 3.19 mPa·s;

[0126] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully infiltrate the positive electrode sheet, the negative electrode sheet and the separator; wherein the electrolyte injection coefficient is 3.10;

[0127] The battery after the electrolyte is injected is charged for the first time and formed;

[0128] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0129] Example 4

[0130] Lithium iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0131] Graphite is used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry is coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet is 99 g / m 2 , compacted density is 1.65g / cm 3 ;

[0132] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0133] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0134] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0135] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate, 45 parts of ethyl methyl carbonate and 20 parts of dimethyl carbonate, and the viscosity of the electrolyte is 3.37 mPa·s;

[0136] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully infiltrate the positive electrode sheet, the negative electrode sheet and the separator; wherein the electrolyte injection coefficient is 3.10;

[0137] The battery after the electrolyte is injected is charged for the first time and formed;

[0138] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0139] Example 5

[0140] Lithium iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0141] Graphite is used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry is coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet is 99 g / m 2 , compacted density is 1.65g / cm 3 ;

[0142] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0143] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0144] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0145] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate, 55 parts of ethyl methyl carbonate and 10 parts of dimethyl carbonate, and the viscosity of the electrolyte is 3.49 mPa·s;

[0146] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully infiltrate the positive electrode sheet, the negative electrode sheet and the separator; wherein the electrolyte injection coefficient is 3.10;

[0147] The battery after the electrolyte is injected is charged for the first time and formed;

[0148] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0149] Example 6

[0150] Lithium iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0151] Graphite is used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry is coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet is 99 g / m 2 , compacted density is 1.65g / cm 3 ;

[0152] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0153] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0154] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0155] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate and 65 parts of ethyl methyl carbonate, and the viscosity of the electrolyte is 3.65 mPa·s;

[0156] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully infiltrate the positive electrode sheet, the negative electrode sheet and the separator; wherein the electrolyte injection coefficient is 3.10;

[0157] The battery after the electrolyte is injected is charged for the first time and formed;

[0158] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0159] Example 7

[0160] Lithium iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0161] Graphite is used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry is coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet is 99 g / m 2 , compacted density is 1.65g / cm 3 ;

[0162] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0163] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0164] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0165] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate, 15 parts of ethyl methyl carbonate and 50 parts of dimethyl carbonate, and the viscosity of the electrolyte is 2.85 mPa·s;

[0166] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully infiltrate the positive electrode sheet, the negative electrode sheet and the separator; wherein the electrolyte injection coefficient is 3.10;

[0167] The battery after the electrolyte is injected is charged for the first time and formed;

[0168] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0169] Example 8

[0170] Lithium iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0171] Graphite is used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry is coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet is 99 g / m 2 , compacted density is 1.65g / cm 3 ;

[0172] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0173] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0174] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0175] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 50 parts of ethyl methyl carbonate and 50 parts of dimethyl carbonate, and the viscosity of the electrolyte is 2.5 mPa·s;

[0176] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully infiltrate the positive electrode sheet, the negative electrode sheet and the separator; wherein the electrolyte injection coefficient is 3.10;

[0177] The battery after the electrolyte is injected is charged for the first time and formed;

[0178] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0179] Example 9

[0180] Lithium iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0181] Graphite is used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry is coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet is 99 g / m 2 , compacted density is 1.65g / cm 3 ;

[0182] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0183] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0184] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0185] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 60 parts of ethylene carbonate and 40 parts of propylene carbonate, and the viscosity of the electrolyte is 4.0 mPa·s;

[0186] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully infiltrate the positive electrode sheet, the negative electrode sheet and the separator; wherein the electrolyte injection coefficient is 3.10;

[0187] The battery after the electrolyte is injected is charged for the first time and formed;

[0188] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0189] Example 10

[0190] Lithium manganese iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 150 g / m 2 , compacted density is 2.2g / cm 3 ;

[0191] Graphite was used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry was coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet was 66 g / m 2 , compacted density is 1.45g / cm 3 ;

[0192] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0193] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0194] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0195] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate, 25 parts of ethyl methyl carbonate and 40 parts of dimethyl carbonate, and the viscosity of the electrolyte is 3.19 mPa·s;

[0196] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully soak the positive electrode sheet, negative electrode sheet and separator; wherein the electrolyte injection coefficient is 3.25;

[0197] The battery after the electrolyte is injected is charged for the first time and formed;

[0198] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0199] Embodiment 11

[0200] Lithium manganese iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.5g / cm 3 ;

[0201] Graphite was used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry was coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet was 97 g / m 2 , compacted density is 1.65g / cm 3 ;

[0202] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0203] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0204] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0205] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate, 25 parts of ethyl methyl carbonate and 40 parts of dimethyl carbonate, and the viscosity of the electrolyte is 3.19 mPa·s;

[0206] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully soak the positive electrode sheet, negative electrode sheet and separator; wherein the electrolyte injection coefficient is 2.5;

[0207] The battery after the electrolyte is injected is charged for the first time and formed;

[0208] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0209] Example 12

[0210] Lithium manganese iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.5g / cm 3 ;

[0211] Graphite was used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry was coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet was 97 g / m 2 , compacted density is 1.65g / cm 3 ;

[0212] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0213] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0214] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0215] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate, 25 parts of ethyl methyl carbonate and 40 parts of dimethyl carbonate, and the viscosity of the electrolyte is 3.19 mPa·s;

[0216] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully soak the positive electrode sheet, negative electrode sheet and separator; wherein the electrolyte injection coefficient is 4.5;

[0217] The battery after the electrolyte is injected is charged for the first time and formed;

[0218] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0219] Embodiment 13

[0220] Lithium iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0221] Graphite is used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry is coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet is 99 g / m 2 , compacted density is 1.65g / cm 3 ;

[0222] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0223] The cut positive electrode sheet, negative electrode sheet and separator are arranged in the order of "positive electrode sheet-separator-negative electrode sheet", and then wound by a winding machine to form a wound battery cell; wherein the separator adopts a "7+2+2" mixed coating separator, that is, a mixed coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0224] The wound battery cell is placed in the battery case and then vacuum-baked to remove moisture from the battery;

[0225] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 30 parts of ethylene carbonate, 5 parts of propylene carbonate, 35 parts of ethyl methyl carbonate and 30 parts of dimethyl carbonate, and the viscosity of the electrolyte is 3.24 mPa·s;

[0226] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully infiltrate the positive electrode sheet, the negative electrode sheet and the separator; wherein the electrolyte injection coefficient is 3.10;

[0227] The battery after the electrolyte is injected is charged for the first time and formed;

[0228] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0229] Comparative Example 1

[0230] Lithium iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0231] Graphite is used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry is coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet is 99 g / m 2 , compacted density is 1.65g / cm 3 ;

[0232] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0233] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0234] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0235] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 60 parts of ethylene carbonate and 40 parts of propylene carbonate, and the viscosity of the electrolyte is 4.0 mPa·s;

[0236] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully soak the positive electrode sheet, negative electrode sheet and separator; wherein the electrolyte injection coefficient is 2.5;

[0237] The battery after the electrolyte is injected is charged for the first time and formed;

[0238] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0239] Comparative Example 2

[0240] Lithium manganese iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 150 g / m 2 , compacted density is 2.2g / cm 3 ;

[0241] Graphite was used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry was coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet was 66 g / m 2 , compacted density is 1.45g / cm 3 ;

[0242] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0243] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0244] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0245] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 60 parts of ethylene carbonate and 40 parts of propylene carbonate, and the viscosity of the electrolyte is 4.0 mPa·s;

[0246] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully soak the positive electrode sheet, negative electrode sheet and separator; wherein the electrolyte injection coefficient is 2.5;

[0247] The battery after the electrolyte is injected is charged for the first time and formed;

[0248] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0249] Comparative Example 3

[0250] Lithium manganese iron phosphate was used as the positive electrode active material to prepare the positive electrode slurry, and the positive electrode slurry was coated on a copper foil with a thickness of 5 μm to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet was 210 g / m 2 , compacted density is 2.55g / cm 3 ;

[0251] Graphite was used as the negative electrode active material to prepare the negative electrode slurry, and the negative electrode slurry was coated on an aluminum foil with a thickness of 12 μm to obtain a negative electrode sheet; wherein the single-sided surface density of the negative electrode sheet was 93 g / m 2 , compacted density is 1.65g / cm 3 ;

[0252] Cutting the positive electrode sheet and the negative electrode sheet into electrode sheets of size;

[0253] The cut positive electrode sheet, negative electrode sheet and separator are stacked together layer by layer in the order of "positive electrode sheet-separator-negative electrode sheet" to form a laminated battery cell; wherein the separator adopts a "7+2+2" mixed-coating separator, that is, a mixed-coating separator with a base film thickness of 7μm and coatings on both sides of 2μm;

[0254] The laminated battery cells are placed in the battery casing, and then vacuum baked to remove moisture from the battery;

[0255] Dissolving lithium bis(fluorosulfonyl)imide (LiFSI) and lithium hexafluorophosphate (LiPF6) in a solvent to obtain an electrolyte; wherein the concentrations of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate are both 0.5 mol / L, the solvent comprises the following components in parts by weight: 60 parts of ethylene carbonate and 40 parts of propylene carbonate, and the viscosity of the electrolyte is 4.0 mPa·s;

[0256] Inject the electrolyte into the vacuum-baked battery and let it stand for 10 hours to allow the electrolyte to fully soak the positive electrode sheet, negative electrode sheet and separator; wherein the electrolyte injection coefficient is 2.5;

[0257] The battery after the electrolyte is injected is charged for the first time and formed;

[0258] An insulating film is attached to the formed battery to prevent the positive and negative electrodes from directly contacting each other.

[0259] The batteries prepared in Examples 1-13 and Comparative Examples 1-3 were subjected to performance tests, including interface lithium deposition test, direct current internal resistance (DCR) test and cycle performance test.

[0260] The method used to test the lithium deposition on the interface is as follows: the battery is fully charged and disassembled after it is off the production line, and the lithium deposition on the interface is observed and graded into no lithium deposition, slight lithium deposition (lithium deposition area is less than 0.5cm 2 ), moderate lithium deposition (lithium deposition area 0.5cm 2 -1.0cm 2 ), severe lithium deposition (lithium deposition area is greater than 1cm 2 ). Full charge conditions are: at 25°C, charge at a constant current of 0.33C to the cut-off voltage (the cut-off voltage of the battery with lithium iron phosphate as the positive electrode active material is 3.65V, and the cut-off voltage of the battery with lithium manganese iron phosphate as the positive electrode active material is LMFP4.2V), then change to constant voltage charging with a cut-off current of 0.05C.

[0261] The DCR test method is: fully charge the battery at 25℃, leave it for 0.5h, then fully discharge the battery, and record the discharge capacity Q. Fully charge the battery again, leave it for 0.5h, then discharge it at 0.1C for 0.5Q, leave it for 1h, record the voltage at this time as V0, then discharge it at 1C for 30s, record the voltage V1 and current I at the end of discharge, then DCR = (V0-V1) / I, the unit is converted to mΩ. The full discharge condition is: discharge to 2.5V at 1C at 25℃.

[0262] The cycle performance test method is: fully charge and discharge the battery at 25°C, and record the capacity retention rate at 500, 1000 and 3000 cycles.

[0263] The test results are shown in Table 1:

[0264] Table 1 Comparison of battery performance in different embodiments and comparative examples

[0265]

[0266] After calculation, the positive electrode compaction density, electrolyte viscosity and electrolyte injection coefficient of the battery in Examples 1-13 can all satisfy the formula: However, the compaction density of the positive electrode sheet, the electrolyte viscosity and the electrolyte injection coefficient of the battery in Comparative Examples 1-3 cannot satisfy the formula

[0267] It can be seen from Table 1 that for batteries with high compaction systems, when the compaction density of the positive electrode sheet, the electrolyte viscosity and the electrolyte injection coefficient meet the requirements of this application, the kinetic performance and the cycle performance are both good, which is a significant improvement over the prior art.

[0268] The embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A battery, characterized in that: Including positive electrode sheet, negative electrode sheet and electrolyte; The battery satisfies the following formula: Wherein, V represents the viscosity of the electrolyte, in mPa·s; PD represents the compaction density of the positive electrode sheet, in g / cm 3 ; C represents the injection coefficient of the electrolyte, and the unit is g / Ah.

2. The battery according to claim 1, characterized in that The battery satisfies the following formula:

3. The battery according to claim 1, characterized in that The viscosity V of the electrolyte and the compaction density PD of the positive electrode sheet satisfy the following formula: V = aPD + b; Among them, -5.0≤a≤-4.0, 10≤b≤20.

4. The battery according to claim 3, characterized in that -4.7≤a≤-4.3, 13≤b≤16.

5. The battery according to any one of claims 1 to 4, characterized in that: The viscosity V of the electrolyte satisfies: 2.5 mPa·s≤V≤4.0 mPa·s; And / or, the electrolyte injection coefficient C satisfies: 2.5g / Ah≤C≤4.5g / Ah; And / or, the compaction density PD of the positive electrode sheet satisfies: 2.2 g / cm 3 ≤PD≤2.8g / cm 3 .

6. The battery according to claim 5, characterized in that The viscosity V of the electrolyte satisfies: 3.2 mPa·s≤V≤3.6 mPa·s; And / or, the electrolyte injection coefficient C satisfies: 2.8g / Ah≤C≤3.5g / Ah; And / or, the compaction density PD of the positive electrode sheet satisfies: 2.3 g / cm 3 ≤PD≤2.6g / cm 3 .

7. The battery according to claim 6, characterized in that The viscosity of the electrolyte is the viscosity of the electrolyte at 25°C; The compaction density of the positive electrode sheet is the compaction density of the positive electrode sheet in an empty state.

8. The battery according to claim 5, characterized in that The electrolyte comprises a lithium salt and a solvent; Wherein, the solvent includes at least one of dimethyl carbonate, ethylene carbonate, propylene carbonate, ethyl methyl carbonate, ethyl acetate and fluoroethylene carbonate.

9. The battery according to claim 8, characterized in that The solvent includes dimethyl carbonate, and the mass proportion of the dimethyl carbonate in the solvent is ≤50%.

10. The battery according to any one of claims 1 to 4 or 6 to 9, characterized in that: The single-sided surface density of the positive electrode sheet is 150g / m 2 -300 g / m 2 .

11. The battery according to any one of claims 1 to 4 or 6 to 9, characterized in that: The positive electrode active material in the positive electrode sheet includes one of lithium iron phosphate and lithium manganese iron phosphate.

12. The battery according to any one of claims 1 to 4 or 6 to 9, characterized in that: The negative electrode active material in the negative electrode sheet includes graphite; And / or, the single surface density of the negative electrode sheet is 80g / m 2 -120 g / m 2 ; And / or, the compaction density of the negative electrode sheet is 1.45 g / cm 3 -1.70g / cm 3 .

13. The battery according to any one of claims 1 to 4 or 6 to 9, characterized in that: The ratio of the negative electrode capacity to the positive electrode capacity of the battery is 1.05-1.

25.

14. The battery according to claim 13, characterized in that The ratio of the negative electrode capacity to the positive electrode capacity of the battery is 1.10-1.

15.

15. The battery according to any one of claims 1 to 4 or 6 to 9, characterized in that: The energy density of the battery is 150Wh / kg-250Wh / kg.

16. A battery pack, characterized in that: Comprising a battery as described in any one of claims 1 to 15.

17. An electrical device, characterized in that: Comprising a battery as described in any one of claims 1 to 15, and / or a battery pack as described in claim 16.

Citation Information

Patent Citations

  • Secondary battery

    CN115548445A

  • Lithium ion battery, battery module, battery pack and electric device

    CN117747952A

  • High-energy-density lithium ion battery and manufacturing method thereof

    CN118352604A

Cited By

  • Battery, battery pack and electric apparatus

    EP4779734A1

  • Battery, battery pack and electric apparatus

    WO2026113101A1